Correlation between Regular Ling Tien Kung Exercise and Uric Acid Level in the Elderly - Lingling Marinda Palupi; Ira Rahmawati; Lucia Retnowati (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
Aging causes physiological changes in all organs in the human body which resulted in body weakness, physical declines and the emergence of age-related conditions such as increased uric acid levels that can cause complications including kidney stones, gout, and rheumatism. Efforts should be encouraged to improve physiological functions in the elderly. These can be a form of care, treatment, healthy lifestyle, or other efforts, such as physical activity. Ling Tien Kung is one of the physical exercises that can be carried out by the older people . The purpose of this study was to determine the correlation between Ling Tien Kung's routine and uric acid levels in the elderly. This study used a cross sectional study design. The Ling Tien Kung interventions was carried out once a week, for 45 minutes for two months. Twenty-five respondents were involved in this study. The sampling technique for selecting respondents was non-probability sampling with a purposive sampling method. Data was analyzed using the Pearson Correlation test. Although the statistical analysis showed that there were no significant correlations between a regular Ling Tien Kung exercise and uric acid levels, some respondents have a lower uric acid level at the end of the study. This may happen because the physical exercise that only be done once a week is not optimal for transporting all the body's metabolism which should then be excreted through the kidneys.